Lessons Learned by Novice Nursing Investigators When Developing and Implementing a Research Protocol - Jeanette Anderson MSN, RNC-O; Antoinette McNeary-Garvin BSN, MSN; Dawn Morales MSN, WHNP-B (SAGE Publishing, 2022)
Introduction This lessons learned paper provides recommendations for novice investigators to consider when writing a research protocol; specifically when it involves clinical staff with varying levels of research experience, multiple departments, and is conducted at a non-academic medical center. It further explores each specific lesson with generalizability to help future novice investigators successfully develop and implement their own research study. Methods There were several lessons learned during the development and implementation of the research teams' original study. These lessons include: (1) Conduct feasibility assessments; (2) Assess external factors; (3) Partner with stakeholder(s); (4) Develop tools that promote transparency; (5) Coordinate with Information Technology personnel; and (6) Engage and educate stakeholders. Conclusion The aim of this study was to determine if unrestricted oral intake of low fat, low residue foods during labor impacts maternal and neonatal outcomes, with the goal of contributing an adequately powered study to the current literature. Due to the challenges experienced in executing this study, the findings were not able to be generalized. However, the challenges encountered are not specific to the original focus of the researchers' study. Each of the lessons are generalizable and can be applied to nursing research. As nurses begin to develop clinical research protocols, utilizing the lessons learned in this paper may help ensure successful implementation and completion of their research.